Comparison of the cytobrush, cytotape and uterine lavage techniques in healthy postpartum cows - RANA, ANCHAL; SINGH, MADHUMEET; KUMAR, PRAVESH; SHARMA, AKSHAY (The Indian Journal of Animal Sciences, 2020)
This study was conducted to compare the accuracy of three different techniques of endometrial cytology to diagnose sub-clinical endometritis in dairy cows. Postpartum dairy cows (21) with history of normal calving were selected for obtaining endometrial samples at weekly interval from day 14 to 42 postpartum. In each cow, samples were obtained in a sequential manner, first with the cytotape, then with the cytobrush followed by uterine lavage. Smears were stained with Giemsa stain method. Parameters used to evaluate these techniques were; presence of polymorphoneutophils (%), total cellularity, red blood cell contamination and quality of the smears. No difference was recorded between the three techniques in % polymorphoneutrophils recovered. All techniques provided diagnostic samples; however, cytotape yielded the highest quality sample. On the other hand, cytobrush and cytotape methods yielded similar total cellularity (P=0.3781), uterine lavage yielded significantly (P<0.01) less number of total cells than other two techniques. Cytotape produced more intact cells than cytobrush and uterine lavage (P<0.05) and red blood cells’ contamination was found high in cytobrush and uterine lavage techniques (P<0.05). Distorted cells were significantly (P<0.01) more frequent in smears obtained by uterine lavage. Also, uterine lavage technique is time consuming and required 2-3 assistant than other two techniques. Hence, cytotape was found to be comparatively the best technique to obtain endometrial cytology samples.